'Happy' drug survival of adalimumab, etanercept and ustekinumab in psoriasis in daily practice care: results from the BioCAPTURE network. (3rd October 2014) - van den Reek, J.M.P.A.; Zweegers, J.; Kievit, W.; Otero, M.E.; van Lümig, P.P.M.; Driessen, R.J.B.; Ossenkoppele, P.M.; Njoo, M.D.; Mommers, J.M.; Koetsier, M.I.A.; Arnold, W.P.; Sybrandy‐Fleuren, B.A.M.; et al.
Summary Background Drug survival is a marker for treatment success. To date, no analyses relating dermatological quality‐of‐life measures to drug survival have been published. Objectives (i) To describe 1‐year drug survival for adalimumab, etanercept and ustekinumab in a daily practice psoriasis cohort, and (ii) to introduce the concept of 'happy' drug survival, defined as Dermatology Life Quality Index (DLQI) ≤ 5 combined with being 'on drug' at a specific time point. Methods Data were extracted from a prospective registry. Drug survival was analysed using Kaplan–Meier estimates. 'Happy' drug survival was calculated, with data split into 'happy' (DLQI ≤ 5) vs. 'unhappy' (DLQI > 5) at baseline and months 3, 6, 9 and 12. Results 249 treatment episodes were included (101 adalimumab, 82 etanercept, 66 ustekinumab). The 1‐year drug survival rates for ustekinumab, adalimumab and etanercept were 85%, 74% and 68%, respectively. Ustekinumab showed a better confounder‐corrected drug survival vs. etanercept [hazard ratio (HR) 3·8, P = 0·02] and a trend towards better survival vs. adalimumab (HR 2·3, P = 0·1). At baseline, the majority (n = 115, 73%) was considered 'unhappy' and a minority 'happy' (n = 42, 27%) (ratio 'happy':'unhappy' was 1 : 2.7). The percentage of treatment episodes with 'happy' on‐drug patients increased to 79% after 1 year. Conclusions Ustekinumab showed a better overall drug survival than etanercept, and a trend towards a better overall drug survival than adalimumab. After 1 year, patients reported to be 'happy' in 79% of episodes and 'unhappy' in 21%. We introduced the new concept of 'happy' drug survival because the proportion of on‐drug patients with good quality of life is an important indicator for treatment success.